Long-Term Benefits of Periodontal Regeneration in Severely Compromised Teeth: A Retrospective Case Series - James R. Collins; Nathalia Vilela; Claudio M. Pannuti (Case Reports in Dentistry)
Periodontal regeneration (PR) could represent a viable treatment alternative for severely compromised teeth. This case series presents the long-term benefits of PR with up to 13 years of follow-up. A total of six teeth in five patients were treated for intrabony defects using PR. The treatment involved the elevation of a mucoperiosteal flap, root instrumentation, and filling the bony defect with bone substitutes. Following PR, a significant reduction in probing depth (PD) was observed (mean 9.5±1.87 mm; p=0.03) along with a statistically significant gain in clinical attachment level (CAL) (mean 8.33±1.03 mm; p=0.03). Radiographic bone defect fill at the defect site was also verified (mean 9.67±2.25 mm; p=0.03). This case series demonstrated that PR led to reduced PD with minimal gingival recession, gain in CAL, and bone fill at defect sites, even in complex periodontal defects extending to the apical portion of the root, over a follow-up period of up to 13 years, indicating it as an effective and predictable treatment alternative.